GAYA KOMUNIKASI KEPEMIMPINAN DALAM ORGANISASI PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DI DESA TERANGMAS KABUPATEN KUDUS - Rizkiyatus Shalihah Shalihah (Media Bahasa, Sastra, dan Budaya Wahana, 2023)
Leadership communication plays an important role in the Family Welfare Empowerment Organization (PKK). With this communication style, it can facilitate the implementation of empowerment programs in this organization. Thus the purpose of this study is to examine the Leadership Communication Style of Family Welfare Empowerment (PKK) in Terangmas Village, Kudus Regency. The research method used is a descriptive qualitative method. Data were taken from literature studies and field studies which were carried out by observing and interviewing one of the members of the PKK organization. In analyzing the data, the researcher uses an interactive model from Miles and Huberman which includes data classification, data appearance, and data conclusion. Based on the results of the study, it was found that the head of the PKK in Terangmas Village used the Equalitarian Style, Structuring Style, Dynamic Style, Relinquishing Style, and Withdrawal Style. Controlling Style is not used because it is not a mutual agreement. Then it is accompanied by the function of the style of communication carried out by the head of the Village PKK Terangmas which includes regulatory functions, informative functions, persuasive functions, and integrative functions.